Formulasi dan Uji Stabilitas Fisik Sediaan Body Scrub Bengkuang (Pachyrhizus erosus) dengan Variasi Konsentrasi Emulgator: Formulation and Physical Stability Tests of Jicama (Pachyrhizus erosus) Body Scrub with Variation of Emulgator Concentrations - Lucy Laila Rahma; Linda Suryanti; Nur Cholis Majid (UIMA Press, 2023)
Jicama tubers (Pachyrhizus erosus) contain antioxidants, including vitamin C, flavonoids, saponins, phenolic compounds. In this study the aims were to formulate and evaluate the stability of a body scrub cream of jicama starch with varying concentrations of 16%, 15, and 14% stearic acid emulsifiers, and 2%, 3%, and 4% triethanolamine. This research method was carried out in a laboratory experiment to determine variations in the concentration of stearic acid and triethanolamine emulsifiers. In addition, observations were made to evaluate the physical quality of the organoleptic test preparations, homogeneity, pH, emulsion type, and physical stability using the accelerated cycling test method. The results of this study indicate that there is an effect of different concentrations of stearic acid and triethanolamine on FI which has a denser form than FII and FIII, after 6 storage cycles FII and FIII change color to yellowish white. This shows that the formulation has the best properties for body scrub cream preparations, is stable and meets the requirements based on organoleptic tests, homogeneity tests, pH tests with a standard facial skin pH of 4.5-7, emulsion type tests, and 12-day stability tests. phase completion occurs, namely FI with a concentration of 16% stearic acid and 2% triethanolamine.